Hemorrhagic gastric ulcer in a patient with Behcet's disease successfully treated with infliximab. Issue 1 (15th December 2022) - Fujiwara, Shun; Kawamoto, Ami; Motobayashi, Maiko; Hibiya, Shuji; Takenaka, Kento; Shimizu, Hiromichi; Saito, Eiko; Fujii, Toshimitsu; Nagahori, Masakazu; Kawata, Daisuke; Umezawa, Natsuka; Hosoya, Tadashi; et al.
Abstract: Behcet's disease (BD) is a multisystem immune‐mediated inflammatory disorder that occasionally involves the gastrointestinal tract. Reports on gastrointestinal involvement of BD are relatively rare, of which gastroduodenal involvement is particularly rare. Endoscopic features of gastroduodenal lesions are unknown, and treatment strategies have not been established. In this report, we present the case of a 72‐year‐old female with gastrointestinal BD who presented with extensive gastroduodenal ulcers and hematemesis that were resistant to colchicine and corticosteroid treatment, which were subsequently successfully treated with infliximab. We also review the current literature on the gastroduodenal involvement of BD. Although rare, the case highlights the importance of being aware of upper gastrointestinal manifestations of BD, as well as demonstrating the potential of infliximab to treat corticosteroid‐resistant cases.